PENGARUH MOTIVASI TERHADAP HUBUNGAN KOMPLEKSITAS TUGAS, GAYA KEPEMIMPINAN DENGAN KINERJA AUDITOR - Erwina, Erwina; Andreas, Andreas; Hardi, Hardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract This research intent to test the effect of Motivation on the relationship between Task Complexity, Leadership style with Auditor Performance on BPK Riau Province delegation. The data was collected using a questionnaire survey, the sample in this study were 47 respondents. Data processing used SPSS version 16. The regression equation used simple linear regression and multiple regression, this test is often called the Moderated Regression Analysis (MRA). The results of the interaction of task complexity and motivation have negativ affect for the performance of the auditor, with a value of 63%, meanwhile its rest 37 % regarded by other variables, it mean the height auditor’s task complexity BPK Riau Province delegation in work will reduce the motivation in work and ensue auditor performance decrease that resulting. Meanwhile result of leadership style interaction and motivation have positive ascendant to auditor performance, with point as big as 69 % auditor performance regarded by leadership style, motivation and leadership style interaction by motivates, meanwhile its rest 31 % regarded by other variables, it mean that leadership suitable will inspire motivate auditor for working so increases BPK'S auditor performance Riau Province delegation.